Relative Efficiency of Cochlear Hydrops Analysis Masking Procedure and Cervical Vestibular Evoked Myogenic Potential in Identification of Meniere's Disease. (22nd February 2015) - Singh, Niraj Kumar; Krishnamurthy, Rahul; Premkumar, Priya Karimuddanahally
Abstract : Cervical vestibular evoked myogenic potential (cVEMP) and cochlear hydrops analysis masking procedure (CHAMP) have both shown sensitivity in identifying Meniere's disease. However none of the previous reports have compared the two tests for their relative efficacy in identifying Meniere's disease. Hence the present study aimed to compare the efficiency of cVEMP and CHAMP in evaluating Meniere's disease. The study included 58 individuals with unilateral definite Meniere's disease and an equal number of age and gender matched healthy individuals. cVEMP corresponding to 500 Hz tone burst was recorded from ipsilateral sternocleidomastoid muscle and CHAMP was acquired from the conventional electrode sites for single channel auditory brainstem response recording using a default protocol of the Biologic Navigator Pro evoked potential system. Both cVEMP and CHAMP showed statistically significant differences between the groups (P < 0.05 ). The receiver operating curves revealed 100% sensitivity and specificity for CHAMP as against 70.7% sensitivity and 100% specificity for cVEMP in identifying Meniere's disease. Therefore, CHAMP appears to be the test of choice provided the degree of hearing loss does not exceed a moderate degree. cVEMP could be used for all degrees of hearing losses, but with slight constraint on the sensitivity.